Status report on water resources availability, accessibility and technology needs for addressing water security challenges in Dolo Ado and Bokolmayo districts, Somali Regional State, Ethiopia - Assefa, T. T.; Taye, Meron Teferi; Ebrahim, Girma Yimer; Ruckstuhl, Sandra (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2024)
Adapting to and mitigating the impacts of extreme weather and climate change in fragile environments requires addressing key questions on the status of water availability, accessibility, and technology needs. The primary goal of this research is to provide comprehensive data and actionable insights to support organizations such as the World Food Programme (WFP) and other stakeholders in developing effective strategies for water management, enhancing resilience, and ensuring water access for host communities, refugees, and internally displaced people (IDPs). This study focused on the Dolo Ado and Bokolmayo districts of Ethiopia, which are parts of the Genale Dawa River basin and the Somali Regional State that are categorized as fragile environments with a high degree of sensitivity to climate extremes.